Burnout and post-traumatic stress disorder in frontline nurses during the COVID-19 pandemic: a systematic literature review and meta-analysis of studies published in 2020: COVID-19, burnout, and PTSD in nurses - Caruso, Rosario; Annaloro, Chiara; Arrigoni, Cristina; Ghizzardi, Greta; Dellafiore, Federica; Magon, Arianna; Maga, Giulia; Nania, Tiziana; Pittella, Francesco; Villa, Giulia (Acta Biomedica Atenei Parmensis, 2021)
This study aimed to systematically synthesize evidence regarding burnout and post-traumatic stress disorder (PTSD) among nurses engaged in the frontline during the COVID-19 pandemic, highlighting their risk and protective factors. The specific literature on nurses’ mental health outcomes still remains not synthesized. A systematic review was performed (PROSPERO: CRD42021227939), searching literature published in 2020 on Pubmed, Scopus, CINAHL, and PsycInfo. We quantitatively pooled means of included studies measuring burnout and PTSD with the same tools. Twenty-five studies were included in this review. Seven (3766 nurses) were included in the meta-analysis for estimating means of depersonalization and emotional exhaustion assessed using the Maslach Burnout Inventory, respectively: 7,40 (95%CI=6,00-8,80) and 22,82 (95%CI=19,24-26,41). Likely, 12 studies were used to estimate two pooled means for PTSD, one for six studies adopting the Impact of Event Scale-Revised (1551 nurses), and six adopting the PTSD Scale for DSM-5 (8547 nurses). The main risk and protective factors of both outcomes were female sex and younger age, work-related variables, and physical and mental factors, such as concerns, skin lesions from wearing personal protective equipment. This systematic review portrayed the situation described in literature during 2020 on nurses’ burnout and PTSD during the COVID-19 pandemic. Although the outcomes’ levels described in the included studies are diverse, the broad situation appears alarming, and supportive multi-level strategies, considering individual and system-level, should be planned to decrease the described worsening scenario within the clinical settings avoid middle and long-term negative consequences.